2018
DOI: 10.5867/medwave.2018.03.7206
|View full text |Cite
|
Sign up to set email alerts
|

Should systemic corticosteroids be used for bronchiolitis?

Abstract: We identified four systematic reviews, including 20 randomized trials overall. We concluded the use of systemic corticosteroids has no benefit for the treatment of bronchiolitis, even for patients with mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In our study, 95.35% of the patients received either corticosteroids, antibiotics, or salbutamol nebulization, translating into poor adherence to management guidelines in only 4.65% of cases. Despite the fact that several authors [ 52 , 53 ] and expert societies [ 14 , 20 ] have reported that corticosteroids have no added benefits in the management of acute bronchiolitis, it was administered in more than 70% of patients in this study. According to an Italian study, four out of ten paediatricians are aware of recommended diagnostic criteria for acute bronchiolitis, however, 39.64% still prescribe bronchodilators, while 64.52% prescribe systemic corticosteroids [ 54 ].…”
Section: Discussionmentioning
confidence: 95%
“…In our study, 95.35% of the patients received either corticosteroids, antibiotics, or salbutamol nebulization, translating into poor adherence to management guidelines in only 4.65% of cases. Despite the fact that several authors [ 52 , 53 ] and expert societies [ 14 , 20 ] have reported that corticosteroids have no added benefits in the management of acute bronchiolitis, it was administered in more than 70% of patients in this study. According to an Italian study, four out of ten paediatricians are aware of recommended diagnostic criteria for acute bronchiolitis, however, 39.64% still prescribe bronchodilators, while 64.52% prescribe systemic corticosteroids [ 54 ].…”
Section: Discussionmentioning
confidence: 95%